The detection of urinary viruses is associated with aggravated symptoms and altered bacteriome in female with overactive bladder - Sun, Qi; Li, Leqian; Zhou, Hao; Wu, Ying; Gao, Yubo; Wu, Bingyi; Qiu, Yifeng; Zhou, Zhipeng; Song, Qixiang; Zhao, Jie; Wu, Peng (Frontiers in Microbiology, 2022)
Although it is known that changes in bacterial components of the urinary microbiome are associated with overactive bladder (OAB), the specific role of viruses is still insufficiently investigated. The aim of the present study is to evaluate the role of urinary viruses in woman with OAB, and analyze the potential relationship between viruses, bacteria and disease. Catheterized urine samples were collected from 55 women with OAB and 18 control individuals. OAB patients fulfilling the following criteria were considered eligible for this study: female, 18 years of age or older; presented with classic OAB symptoms defined by the International Continence Society; and OAB Symptom Score (OABSS) total score ≥ 3 points and question 3 (urgency) score ≥ 2 points. Based on results of metagenomic next-generation sequencing (mNGS), all participants were divided into virus-infected and virus-uninfected groups for analysis. The results of mNGS showed that the diversity of the OAB group was lower than that of the control group when focused on bacterial sequences, which was consistent with our previous study. According to the questionnaire filled out by the patients, OABSS and 8-item OAB questionnaire, female OAB patients who had viruses detected in their urine had more severe symptoms. In parallel, John Cunningham virus (mainly subtype 7 and subtype 2) was the most frequently detected virus in urine. Correlation analysis indicated that risk factors for virus infection in OAB patients include age, habit of holding urine and pelvic surgery history. Given our preliminary data, viral infection can aggravate OAB severity and affect the composition of bacterial. Further research is required to explain how viral infections can aggravate OAB patient symptoms and cause bacterial changes.